Toy library a feasibility study for Marikina City - Deasis, Susannah V. (2012)
This is a descriptive-feasibility study that determined the viability of setting up the first ever statutory toy library in Marikina City according to its market, technical, and financial aspect. A total of 200 parent/guardian respondents were interviewed in 2005. Respondents were evenly distributed among the 15 barangays of Marikina City according to its population percentage.